2009
DOI: 10.1038/nm.1997
|View full text |Cite|
|
Sign up to set email alerts
|

GOAT links dietary lipids with the endocrine control of energy balance

Abstract: CNS nutrient sensing and afferent endocrine signalling are established as parallel systems communicating metabolic status and energy availability in vertebrates. The only afferent endocrine signal known to require modification with a fatty acid side chain is the orexigenic hormone ghrelin. We find that the ghrelin O-acyl transferase (GOAT) which is essential for ghrelin acylation, is regulated by nutrient availability, depends on specific dietary lipids as acylation substrates and modulates body fat mass in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
337
1
15

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 364 publications
(370 citation statements)
references
References 22 publications
17
337
1
15
Order By: Relevance
“…their effects on PP release from islets) will reflect not only the receptor make-up of the target cells but also the circulating concentration of all three peptides, acyl ghrelin, desacyl ghrelin and obestatin. Plasma desacyl ghrelin levels are typically 5-10-fold higher than acyl ghrelin in rat, mouse and man (desacyl ghrelin levels in rodents ranging between 150-600 pmol/l while acyl ghrelin levels range between 10-50 pmol/l) (8,10). Obestatin levels are also higher than acyl ghrelin levels, ranging between 100-800 pmol/l (9,21,56).…”
Section: Implication Of the Findings With Respect To The Functional Rmentioning
confidence: 99%
See 3 more Smart Citations
“…their effects on PP release from islets) will reflect not only the receptor make-up of the target cells but also the circulating concentration of all three peptides, acyl ghrelin, desacyl ghrelin and obestatin. Plasma desacyl ghrelin levels are typically 5-10-fold higher than acyl ghrelin in rat, mouse and man (desacyl ghrelin levels in rodents ranging between 150-600 pmol/l while acyl ghrelin levels range between 10-50 pmol/l) (8,10). Obestatin levels are also higher than acyl ghrelin levels, ranging between 100-800 pmol/l (9,21,56).…”
Section: Implication Of the Findings With Respect To The Functional Rmentioning
confidence: 99%
“…Hatched areas in the Fig. show the range of reported blood concentrations of obestatin, acyl ghrelin and desacyl ghrelin in fasted or fed mice and rats (1,4,(7)(8)(9)(10)21). From the concentrationresponse curves it seems that the circulating concentrations of both obestatin and acyl ghrelin will cause 80-90 % suppression of spontaneous PP release.…”
Section: Implication Of the Findings With Respect To The Functional Rmentioning
confidence: 99%
See 2 more Smart Citations
“…2001bNakazato et al 2001) and its acylation is considered necessary for its actions via GHSR1a (the functional variant of GHSR) (Howard et al 1996; Kojima et al 1999). Recently, several groups identified ghrelin O-Acyltransferase (GOAT), a membrane-bound enzyme that transfers octanoate from octanoyl CoA to serine-3 of ghrelin, forming an acyl ester (Gutierrez et al 2008;Yang et al 2008) and a recent study observed that GOAT links dietary lipids with the endocrine control of energy balance (Kirchner et al 2009). …”
Section: Introductionmentioning
confidence: 99%